Utilisation Of Superheated Steam And Torrefacto Roasting On Quality Attributes Of Black Seed (Nigella Sativa) For Beverage Application - Veeriah, Harivaindaran K. (2024)
Nigella sativa, known as black seed, has many health benefits and is typically roasted prior to consumption. This causes detrimental quality loss, thus, an innovative method such as superheated steam (SHS) and torrefacto roasting may be advantageous. This research aims to develop a beverage from SHS torrefacto (TR) roasted black seeds. In the first phase, SHS was applied to black seeds at 150℃, 200℃ and 250℃ for 10, 15, and 20 mins at each temperature then compared to convection roasting at the same parameters for lipid oxidation, proximate, antioxidants, and essential oils. Results indicated that SHS roasted seeds yielded more oil (24.83 % vs only 23.23 % oil for convection) and had better peroxide value (highest value for convection, 84.00 versus SHS, 48.00 meq O2/kg of oil), p-anisidine value (highest value; for convection, 28.36 versus SHS, 23.73), FRAP values (SHS; 327 to 435 mM FeSO4/g sample, convection; 301 to 356 mM FeSO4/g sample), and DPPH scavenging capacity (SHS; 92.45 to 69.97 % inhibition, convection; 92.08 to 65.81 % inhibition). Results also indicate unsuitable extraction method and poor seed quality since oil oxidative analysis results were all above standard acceptable levels. Convection roasting also caused loss of thymoquinone, an important characteristic component of black seed essential oil. In the second phase, black seeds were TR and SHS roasted at 220℃ for 10 min. This roasting time and temperature was derived via response surface methodology for maximum antioxidant capacity.